Effectiveness of peer counseling and membership in breastfeeding support groups in promoting optimal breastfeeding behaviors in the Philippines - Ofelia P. Saniel; Veincent Christian F. Pepito; Arianna Maever L. Amit (BMC, 2021)
Abstract Background The prevalence of early initiation of breastfeeding and exclusive breastfeeding (EBF) at 6 months remain low in the Philippines. To help meet the 90% early initiation of breastfeeding target and to improve infant and young child feeding practices in the Philippines, the Millennium Development Goals - Fund 2030 Joint Programme (JP) on Ensuring Food Security and Nutrition for Children 0-24 months old was implemented. We aimed to determine the effectiveness of visits by peer counselors during pregnancy and after delivery, and membership in breastfeeding support groups in promoting these optimal breastfeeding practices. Methods We used data from the Endline Survey of the JP to study the effects of prenatal and postnatal peer counselor visits, and membership in breastfeeding support groups, and their possible interactions with initiation of breastfeeding within 1 hour of birth among children aged 0 to 24 months and EBF at 6 months among children aged 6 to 24 months, while adjusting for confounding. We used logistic regression methods for survey data to assess these associations. Results Of the 2343 mother-infant pairs, only 1500 (63.1%) practiced early initiation of breastfeeding. Of the 1865 children aged 6 months or older, only 621 (34.7%) were exclusively breastfed at 6 months. After adjusting for confounding variables, there was no strong evidence that peer counselor visits were associated with early initiation or EBF at 6 months. However, members of breastfeeding support groups had 1.49 times higher odds of early initiation of breastfeeding (95% CI [Confidence Interval] 1.12, 1.98) and 1.65 times higher odds of EBF (95% CI 1.20, 2.24) compared to those who were not members of breastfeeding support groups. There was no interaction between the different exposure variables and early initiation and EBF at 6 months. Conclusions Our findings suggest breastfeeding support groups may be institutionalized to promote both early initiation of breastfeeding and EBF in the Philippines, while the role of peer counselors in promoting optimal breastfeeding behaviors should be further reviewed. Our suggestion to integrate non-healthcare professionals to promote early initiation of breastfeeding and EBF could be tested in future intervention studies.